Do agri‐environment schemes result in improved water quality?. Issue 2 (15th September 2016) - Jones, J. Iwan; Murphy, John F.; Anthony, Steven G.; Arnold, Amanda; Blackburn, John H.; Duerdoth, Chas P.; Hawczak, Adrianna; Hughes, Greg O.; Pretty, James L.; Scarlett, Peter M.; Gooday, Richard D.; Zhang, Yusheng S.; et al.
Summary: Improved water quality, through a reduction in diffuse pollution from agricultural sources, is an expected benefit of agri‐environment schemes, but this has yet to be demonstrated in practice. Here, we evaluate the impact of Welsh agri‐environment schemes on water quality and freshwater ecosystem condition through a combined monitoring and modelling framework. To determine the influence of the agri‐environment schemes on ecosystem condition, spatially independent catchments dominated by a single scheme (>40% of catchment) were compared to control catchments dominated (>70%) by agricultural land that was not part of any scheme. Biological indicators of water quality were monitored at the outfall of each catchment and a spatially explicit modelling framework of diffuse pollutant emissions applied to each of the 80 catchments. Direct comparison (scheme/non‐scheme) was unable to identify any significant effect of agri‐environment scheme participation. However, derived biological indicators that reflected organic pollution, eutrophication and pesticide run‐off were strongly correlated with modelled concentrations of corresponding diffuse pollutants, thus providing a ground‐truth for the models. Scenarios that assessed the correct counterfactuals (i.e. the influence of scheme entry on pollutant output) were developed for the whole of Wales. The models indicated an important effect of scheme entry on water quality, but this effect was not evenly distributed across the landscape. Synthesis and applications . Our results indicate that agri‐environment schemes can deliver improvements in water quality, through a reduction in diffuse pollution from agricultural sources. However, it is not easy to demonstrate scheme effectiveness; the combination of field survey and modelling used here provides a framework for addressing these difficulties. A spatially targeted approach for agri‐environment scheme options to protect water resources from diffuse pollution is likely to be most effective at delivering water quality improvements.